2014
DOI: 10.3758/s13421-014-0416-z
|View full text |Cite
|
Sign up to set email alerts
|

Expecting to teach enhances learning and organization of knowledge in free recall of text passages

Abstract: The present research assessed the potential effects of expecting to teach on learning. In two experiments, participants studied passages either in preparation for a later test or in preparation for teaching the passage to another student who would then be tested. In reality, all participants were tested, and no one actually engaged in teaching. Participants expecting to teach produced more complete and better organized free recall of the passage (Experiment 1) and, in general, correctly answered more questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 37 publications
6
77
1
Order By: Relevance
“…Prior research has found that test expectancy (knowing that one will be tested) plays an important role in encoding and long-term retention (Nestojko, Bui, Kornell, & Bjork, 2014;Szpunar, McDermott, & Roediger, 2007;Weinstein et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that test expectancy (knowing that one will be tested) plays an important role in encoding and long-term retention (Nestojko, Bui, Kornell, & Bjork, 2014;Szpunar, McDermott, & Roediger, 2007;Weinstein et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This form of reflective practice has cemented difficult concepts and improved our understandings of them (Nestojko et al, 2014). This practice of teaching to participants outside of our discipline increased our understanding of knowledge translation, a vital tool in communicating research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expectation of teaching content has been found to improve learning and knowledge organisation. Participants expecting to subsequently teach material acquire a better knowledge of material than participants merely expecting to be tested on it (Nestojko, Bui, Kornell, & Bjork, 2014). As mentors we have improved our learning through the facilitation of workshops which focus on enhancing the HDR candidate experience.…”
Section: Teaching Enhances Learningmentioning
confidence: 99%
“…Adaptations of the learning pyramid have been made in different contexts and even with different values for the percentages of learning and retention, being highly relevant here the one shared by The World Bank (n.d.), placing the retention rate-and therefore the learning-of teaching at the 90%, the highest of all the shown ones. Although the learning pyramid seems to lack the evidence needed to support the use of particular percentages and the implied comparison between ways to deal with the information acquired (Letrud & Hernes, 2016) the value of teaching as a tool for learning is supported beyond the pyramid framework, as evidence in Cortese (2005), Chase, Chin, Oppezzo, andSchwartz (2009), or Nestojko, Bui, Kornell, andBjork (2014) supports. Furthermore, there is a whole theory on learning by teaching, known as LdL for its German acronym, as presented by Grzega (2005, Sep).…”
Section: Theoretical Supportmentioning
confidence: 99%